2009
DOI: 10.1039/b900177h
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey of microRNA–transcription factor feed-forward regulatory circuits in human

Abstract: In this work, we describe a computational framework for the genome-wide identification and characterization of mixed transcriptional/post-transcriptional regulatory circuits in humans.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
102
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 53 publications
(188 reference statements)
2
102
0
Order By: Relevance
“…Genome-scale analyses revealed that feedback and feedforward loops that contain miRNAs are also recurrent network motifs in large gene networks (Tsang et al, 2007;Martinez et al, 2008;Re et al, 2009), so that miRNAs can provide biological robustness by participating in these loops (Hornstein and Shomron, 2006;Wu et al, 2009a;Herranz and Cohen, 2010;Osella et al, 2011;Pelaez and Carthew, 2012). miRNAs are small (approximately 22 nucleotides) noncoding single-stranded RNAs that regulate gene expression post-transcriptionally.…”
Section: Mirna-containing Circuits Contribute To the Robustness Of Bimentioning
confidence: 99%
“…Genome-scale analyses revealed that feedback and feedforward loops that contain miRNAs are also recurrent network motifs in large gene networks (Tsang et al, 2007;Martinez et al, 2008;Re et al, 2009), so that miRNAs can provide biological robustness by participating in these loops (Hornstein and Shomron, 2006;Wu et al, 2009a;Herranz and Cohen, 2010;Osella et al, 2011;Pelaez and Carthew, 2012). miRNAs are small (approximately 22 nucleotides) noncoding single-stranded RNAs that regulate gene expression post-transcriptionally.…”
Section: Mirna-containing Circuits Contribute To the Robustness Of Bimentioning
confidence: 99%
“…Recently several studies have shown that the transcriptional regulation by transcription factors (TFs) and posttranscriptional regulation by miRNAs are often highly coordinated (Shimoni et al 2007;Tsang et al 2007;Shalgi et al 2007;Re et al 2009;Martinez et al 2008;Martinez and Walhout 2009;Yu et al 2008;Inui et al 2010;Ivey and Srivastava 2010). Of particular relevance is the accumulating evidence that the interplay of miRNAs and transcriptional regulators such as activators and repressors regulates key developmental events and cell fate decisions (Johnston et al 2005;Kim 2007;Fazi 2005;Juan et al 2009;Bracken 2008;Li and Carthew 2005;Visvanathan et al 2007;Xu et al 2009;Zhao et al 2009;Pospisil 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory roles of miRNAs have been a subject of research for the last several years, both experimentally and theoretically (Shimoni et al 2007;Wang and Raghavachari 2011;Levine et al 2007; Levine and Hwa 2008;Mehta et al 2008;Osella et al 2011;Mitarai et al 2009;Bumgarner et al 2009;Iliopoulos et al 2009). Although some of the miRNAs have been well studied, the mechanisms of various functions and biological significance of miRNAs are still not well understood (Bumgarner et al 2009;Iliopoulos et al 2009;Tsang et al 2007;Shalgi et al 2007;Re et al 2009;Martinez et al 2008;Martinez and Walhout 2009;Yu et al 2008;Inui et al 2010;Ivey and Srivastava 2010;Johnston et al 2005;Kim 2007;Fazi 2005;Juan et al 2009;Bracken 2008;Li and Carthew 2005;Visvanathan et al 2007;Xu et al 2009;Zhao et al 2009;Pospisil 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms and consequences of miR deregulation within a cancer cell are still being determined, although it is likely that changes in the levels and the activity of transcriptional regulators and the miR-processing machinery, coupled with alterations in miR copy number, contribute to the overall deregulation of miR expression (Zhang et al, 2006;Selcuklu et al, 2009). There is now evidence for the participation of miR and transcription factor combinations in feedback and feed-forward loops (Tsang et al, 2007;Brosh et al, 2008;Bartel, 2009;Re et al, 2009), and such miR/transcription factor feed-forward loops enhance the robustness and responsiveness of the gene regulation network (Filipowicz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%